Pembelajaran Tematik Integratif IPA dan IPS di Madrasah Ibtidaiyah (MI) dalam Kurikulum 2013 - Muspiroh, Novianti (IAIN Ponorogo, 2016)
This research is inspired by a question: why does curriculum 2013 using integrated thematic learning. To address this question, a philosophical, psychological, and juridical basis should be discussed. By understanding those things, integrated thematic learning is suited with curriculum 2013. As the description above, this study is to focus on how the integrated thematic learning at MI level is implemented because this learning will become a main model that educators should develop the curriculum 2013. Referring to Integrated thematic learning of curriculum 2013, science and social studies are not removed but they are integrated based on theme. Those studies will be topics of all subjects in MI. This integration is done in two points: (1) attitude, skill, and knowledge integration in learning process and (2) integration of basic concepts that are closely related. The theme makes a meaning among basic concepts so the students do not learn partially. Therefore, science and social studies give a whole meaning to the learners as reflected at the available theme: Ø§ÙØ·ÙÙØª ÙØ°Ù Ø§ÙØ¯Ø±Ø§Ø³Ø© Ù Ù Ø§ÙØ³Ø¤Ø§Ù